Economic freedom as a driver for growth in transition - Jenni Pääkkönen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2009)
This paper reviews the political economy view of economic growth in post-communist economies making the transition to free markets, focusing on the role of economic policy and institutions. We test the hypothesis that better institutions, measured in terms of economic freedom, contribute to growth. The empirical results from the cross-section of transition economies confirm this hypothesis. The paper concludes that non-linearities are present in the growth model and that differences arise depending on how economic well-being is defined.
URN:NBN:fi:bof-201408072003
Keywords: O17; O40; O57; 330; growth; institutions; human capital